"En simples physiciens". La perception animale et la connaissance sensible selon Leibniz en 1714 - Vargas, Evelyn (Lexicon philosophicum.)
In his solution to the problem of sensible knowledge, Leibniz seeks to avoid the extreme positions held by the Cartesians and Hobbes. The conceptual distinctions that Leibniz introduces allow him to overcome difficulties raised by his own earlier definitions of sensus. He is consequently able to reconcile the continuity he introduces between animal and human perceptions with the normative and, at the same time, propositional aspects of perceptual judgments. In this paper I will begin by describing his late conception of both human and animal perception, and I will compare this notion with his early notion of perception and the difficulties it gave rise to; finally, I will show the advantages that his new conception can offer for solving the epistemic problem of perception.